Aquatic bacterial diversity: Magnitude, dynamics, and controlling factors. (March 2017) - Shafi, Sana; Kamili, Azra N.; Shah, Manzoor A.; Parray, Javid A.; Bandh, Suhaib A.
Abstract: The primary aspiration in the microbial observatory is to advance the understanding of freshwater bacterioplankton, whose diversity and population dynamics are currently the least understood off all freshwater planktonic organisms. Through identification and characterization of bacterial populations in a suite of fresh water bodies, we are able to gain significant new insight into the ecological niches of bacteria in diverse freshwater ecosystems. Given the facts that lakes and other inland freshwaters play a more critical role in the global carbon budget and that lakes have been described as early indicators of both regional and global environmental change, the role of microbes in these processes is of renewed interest. In this review, general overview will be given highlighting the characteristic features of bacterial species thriving in different water bodies. In the following sections, different cultural approaches vis a vis the controlling factors of bacterial diversity have been elaborated. In the concluding sections, the prospects of aquatic microbial diversity are well mentioned. Highlights: Diversity and population dynamics of freshwater planktonic organisms. Bacteria are the indicators of both regional and global environmental change. Cultural approaches or controlling factors have been directly related with diversity. Nutrient acquisition and environmental factors determine the status of bacterial flora.